2023
DOI: 10.7150/thno.82995
|View full text |Cite
|
Sign up to set email alerts
|

PER2 integrates circadian disruption and pituitary tumorigenesis

Abstract: Rationale:The role of circadian clock in pituitary tumorigenesis remains elusive. Here we investigate whether and how circadian clock modulates the development of pituitary adenomas. Methods and Results: We found altered expression of pituitary clock genes in patients with pituitary adenomas. In particular, PER2 is prominently upregulated. Further, jetlagged mice with PER2 upregulation have accelerated growth of GH3 xenograft tumor. Conversely, loss of Per2 protects mice against developing estrogen-induced pit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…This study found that the proportion of lymphocytes in the afternoon radiotherapy group was significantly higher than that in the morning radiotherapy group, corresponding to higher overall survival and progression-free survival rates in the afternoon radiotherapy group. This seemingly results from the upregulation of Per2 expression during the afternoon period [45] , as studies suggest that Per2 gene knockout corresponds with notable splenic lymphocyte reductions [46] . The onset of glioma is intrinsically linked to circadian clock gene aberrations.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that the proportion of lymphocytes in the afternoon radiotherapy group was significantly higher than that in the morning radiotherapy group, corresponding to higher overall survival and progression-free survival rates in the afternoon radiotherapy group. This seemingly results from the upregulation of Per2 expression during the afternoon period [45] , as studies suggest that Per2 gene knockout corresponds with notable splenic lymphocyte reductions [46] . The onset of glioma is intrinsically linked to circadian clock gene aberrations.…”
Section: Discussionmentioning
confidence: 99%
“…Per2 is the most frequently studied member of the Per family. As a crucial and powerful clock gene, Per2 has been found to be involved in physio/pathological pathways in tissue development ( McQueen et al, 2018 ), cell differentiation ( Huang et al, 2021 ), cell metabolism ( Grimaldi et al, 2010 ), cell aging ( Levine et al, 2020 ), tumor development ( Guo et al, 2023 ), oxidative stress ( Magnone et al, 2014 ), and neurobiological activities ( Sayson et al, 2023 ). For tooth development, PER2 has recently been identified as a potential regulator ( Huang et al, 2021 ; Jiang et al, 2022 ; Zheng et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Four to five percent of pituitary adenomas are associated with clinical syndromes like multiple endocrine neoplasia 1 (Carney complex) and familial isolated pituitary adenoma, whose diverse genetic profiles are still under investigation[ 175 ]. A recent work has revealed the role of PER2 , a key clock gene, in the pathogenesis of pituitary adenomas[ 176 ]. In human tissues obtained from prolactinomas and growth hormone-producing adenomas, the expression of several CGs was dysregulated compared to controls, with PER2 being consistently overexpressed.…”
Section: Circadian Disruption and Clock Genes In Endocrine Tumorsmentioning
confidence: 99%
“…Jet-lagged mice that had been inoculated with GH3 cells exhibited a faster rate of tumor growth that had a time-specific pattern[ 176 ]. The timing of higher cell proliferation was different compared to mice with intact circadian rhythm and correlated with elevated Per2 expression.…”
Section: Circadian Disruption and Clock Genes In Endocrine Tumorsmentioning
confidence: 99%
See 1 more Smart Citation